Gambling and other addictive behaviors among higher education students in Finland—insights from a large-scale survey - Jussi Palomäki; Jussi Palomäki; Sari Castrén; Sari Castrén; Sari Castrén; Niko Männikkö; Niko Männikkö; Tiina Latvala (Frontiers in Psychology)
IntroductionProblem gambling forms a continuum of severity from mild to moderate and severe. While most young individuals who gamble do so responsibly, for some gambling becomes a problem with severe negative consequences. Excessive gambling is strongly linked with substance use and other behavioral addictions, particularly among students.MethodsIn this study we draw from a large sample of higher education students to evaluate the links between gambling behavior, socioeconomic status, mental health, alcohol use and other potentially addictive behaviors. We analyzed our data using post-stratification survey weighted logistic regression modeling.ResultsOur main findings were that (i) students in polytechnics were more prone to gamble and experience harms than university students, (ii) self-perceived problem gambling was significantly associated with alcohol use but not with drug use or smoking, and (iii) compulsive internet use predicted gambling problems but not increased gambling activity.DiscussionOur results underscore the need for early detection of harmful behaviors among students, and early interventions for those with severe problems. Student health checks should be used to screen for harmful gambling habits and difficulties in handling finances.